2019
DOI: 10.1371/journal.pone.0221699
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic, biochemical and genomic variability in generations of the rapeseed (Brassica napus L.) mutant lines obtained via chemical mutagenesis

Abstract: The phenotypic, biochemical and genetic variability was studied in M2-M5 generations of ethyl methansulfonat (EMS, 0.2%) mutagenized rapeseed lines generated from canola, ‘00’, B . napus cv. Vikros. EMS mutagenesis induced extensive diversity in morphological and agronomic traits among mutant progeny resulted in selection of EMS populations of B . napus - and B . rapa- morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 72 publications
(94 reference statements)
0
7
0
Order By: Relevance
“…Dwarfism is one of the most important objectives of banana breeding because dwarf plants have strong resistance to wind or flood disturbances (Cho et al, 2016 ; Wang et al, 2021 ). Recent work found that chemical mutagenesis is capable of inducing dwarf and semi-dwarf mutants from high-stem banana varieties (Aslam et al, 2016 ; Amosova et al, 2019 ). In our study, the gene locus controlling banana plant height was sensitive to the EMS mutagen, leading to abundant dwarf or semi-dwarf mutant offspring obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Dwarfism is one of the most important objectives of banana breeding because dwarf plants have strong resistance to wind or flood disturbances (Cho et al, 2016 ; Wang et al, 2021 ). Recent work found that chemical mutagenesis is capable of inducing dwarf and semi-dwarf mutants from high-stem banana varieties (Aslam et al, 2016 ; Amosova et al, 2019 ). In our study, the gene locus controlling banana plant height was sensitive to the EMS mutagen, leading to abundant dwarf or semi-dwarf mutant offspring obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous EMS mutagenesis studies in B. napus (Wang et al, 2008;Harloff et al, 2012;Amosova et al, 2019) and our examinations of various EMS concentrations on the germination rate, 0.8% EMS was applied in this study. Previous EMS mutagenesis studies in crops usually screened a few thousand mutagenized plants, and numerous mutants have been successfully identified in peanut (Fang et al, 2012), cucumber (Wang et al, 2014), eggplant (Xi-ou et al, 2017), soybean (Espina et al, 2018), rice (Takagi et al, 2015) and B. napus (Wang et al, 2008;Harloff et al, 2012;Amosova et al, 2019). In order to identify adequate mutants for gene cloning and breeding, we generated a M2 population with approximately 100 000 plants in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The creation of mutant materials by EMS produces stable genetic variation at the genome level with a high density of point mutation, and valuable mutants can be directly applied to breeding without gene-modified controversy (Steven et al, 2004). EMS-induced mutagenesis has been widely used in different crops, such as soybean (Lakhssassi et al, 2017;Espina et al, 2018), maize (Lu et al, 2018b), rice (Serrat et al, 2014;Takagi et al, 2015), wheat (Chen et al, 2012), rapeseed (Wang et al, 2008;Harloff et al, 2012;Amosova et al, 2019) and tomato (Shirasawa et al, 2016). EMS-induced mutagenesis has been shown to be an effective way to obtain germplasm resources in the quality breeding of rapeseed, especially in the development of rapeseed cultivars with high oleic acid and low linolenic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, a basic understanding of genomic instability in plants came from IR studies; however, further research has revealed that this type of instability can also occur as a result of other methods used in plant breeding, for instance, physical, chemical, or radiation mutagenesis. Recent studies have shown that stress-inducing factors, such as low concentrations of EMS [ 165 ], herbicides [ 166 ], and salt and heat stress [ 142 ], can also lead to genomic instability.…”
Section: Stress-induced Genomic Instabilitymentioning
confidence: 99%